Long term exposure to low level air pollution and mortality in eight European cohorts within the ELAPSE project: pooled analysis. (1st September 2021) - Strak, Maciej; Weinmayr, Gudrun; Rodopoulou, Sophia; Chen, Jie; de Hoogh, Kees; Andersen, Zorana J; Atkinson, Richard; Bauwelinck, Mariska; Bekkevold, Terese; Bellander, Tom; Boutron-Ruault, Marie-Christine; Brandt, Jørgen; et al.
Abstract: Objective: To investigate the associations between air pollution and mortality, focusing on associations below current European Union, United States, and World Health Organization standards and guidelines. Design: Pooled analysis of eight cohorts. Setting: Multicentre project Effects of Low-Level Air Pollution: A Study in Europe (ELAPSE) in six European countries. Participants: 325 367 adults from the general population recruited mostly in the 1990s or 2000s with detailed lifestyle data. Stratified Cox proportional hazard models were used to analyse the associations between air pollution and mortality. Western Europe-wide land use regression models were used to characterise residential air pollution concentrations of ambient fine particulate matter (PM2.5 ), nitrogen dioxide, ozone, and black carbon. Main outcome measures: Deaths due to natural causes and cause specific mortality. Results: Of 325 367 adults followed-up for an average of 19.5 years, 47 131 deaths were observed. Higher exposure to PM2.5, nitrogen dioxide, and black carbon was associated with significantly increased risk of almost all outcomes. An increase of 5 µg/m 3 in PM2.5 was associated with 13% (95% confidence interval 10.6% to 15.5%) increase in natural deaths; the corresponding figure for a 10 µg/m 3 increase in nitrogen dioxide was 8.6% (7% to 10.2%). Associations with PM2.5, nitrogen dioxide, and black carbon remained significant at low concentrations. For participants with exposures below the US standard of 12 µg/m 3 an increase of 5 µg/m 3 in PM2.5 was associated with 29.6% (14% to 47.4%) increase in natural deaths. Conclusions: Our study contributes to the evidence that outdoor air pollution is associated with mortality even at low pollution levels below the current European and North American standards and WHO guideline values. These findings are therefore an important contribution to the debate about revision of air quality limits, guidelines, and standards, and future assessments by the Global Burden of Disease.